SOSIALISASI AKREDITASI SMP DI DINAS PENDIDIKAN KABUPATEN PACITAN DENGAN PENDEKATAN HOTS - Suryanto, Hadi; Ghofur, Abd.; Youhanita, Ety (STKIP PGRI SITUBONDO, 2025)
Accreditation socialization is a strategic step in building a comprehensive and holistic understanding of the education quality assurance system. In the context of 21st-century education, it is crucial to integrate a learning approach that emphasizes higher-order thinking skills into this socialization process. This article aims to discuss the concept, implementation, and benefits of the HOTS approach in accreditation socialization activities. Using a literature review and a simple case study, this article presents how HOTS can enhance understanding, active participation, and innovation in the accreditation process.